The diaries of Nikolay Punin : 1904-1953 - Punin, N. N. (Nikolaĭ Nikolaevich) (Harry Ransom Humanities Research Center imprint series., 1999)
"This volume presents the first English translation of ten diary notebooks that Punin wrote between 1915 and 1936. Also included are selections from Punin's earlier (1904-1910) and later (1941-1946) diaries, as well as some thirty notes and letters relating to his affair with Anna Akhmatova. These materials offer a rare glimpse into the life of art and artists in Russia, as well as into the intimate relationship of Punin and Akhmatova."